Onion plant development under different soil and climate conditions. I: Vegetative development and absolute growth rate - Klar, A. E.; Pedras, J. F.; Rodrigues, J. D. (Pesquisa Agropecuaria Brasileira, 2014)
The present paper refers to the anion crop (Allium cepa, L.) behavior, on two soils (Soil A- Unidade Experimental and Soil B - Unidade Lageado) and two climates, under different soil water regimes; in the field conditions the treatments were distinguished by the following minimum soil water potentials: -15.0; -0.8; -0.3; -0.15 bars, and daily irrigation; in the greenhouse conditions the following treatments were used: - 15.0; —0.2 bars, and other two daily irrigated; these latter were distinguished by receiving or not the drip irrigation. The treatments with minimum soil water potentials of -0.15 bars allowed the best yields, as in fresh as in dry matter of plants for both soils in the field conditions, however the soil A (thicker texture) was less yielding. In the greenhouse conditions, the soils behaved in the same way, but the daily irrigated treatments were the best, with small advantage for the drip. There was a tendency to decrease the absolute growth rates of the treatments from the highest to the lowest soil water potentials in both soil and climates for the differences between the two first collects; this tendency was mantained in the greenhouse conditions, but with inversion in the field for the differences between the third and the second collects. There was a tendency to decrease from the highest to the lowest soil water potential treaments in field conditions, but the inverse occurred in the greenhouse conditions.